2019
DOI: 10.1145/3355089.3356539
|View full text |Cite
|
Sign up to set email alerts
|

Wirtinger holography for near-eye displays

Abstract: Near-eye displays using holographic projection are emerging as an exciting display approach for virtual and augmented reality at high-resolution without complex optical setups --- shifting optical complexity to computation. While precise phase modulation hardware is becoming available, phase retrieval algorithms are still in their infancy, and holographic display approaches resort to heuristic encoding methods or iterative methods relying on various relaxations. In this work, we depart from such exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 24 publications
0
80
0
Order By: Relevance
“…Note that the normal LED’s aperture is adjusted to 200 μm from 600 μm because 600 μm aperture carries too much resolution reduction that hinders accurate analysis. ( b ) Phase holograms generated by Wirtinger method 46 reconstruct the resolution chart for resolution analysis. Using the experimental results, we estimate the speckle contrast as well as ( c ) the relative contrast function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the normal LED’s aperture is adjusted to 200 μm from 600 μm because 600 μm aperture carries too much resolution reduction that hinders accurate analysis. ( b ) Phase holograms generated by Wirtinger method 46 reconstruct the resolution chart for resolution analysis. Using the experimental results, we estimate the speckle contrast as well as ( c ) the relative contrast function.…”
Section: Resultsmentioning
confidence: 99%
“…6 , where the holograms reconstruct volumetric scenes. Second, we optimize phase-only holograms following the method called Wirtinger holography 46 . We apply 100 iterations for the hologram optimization.…”
Section: Methodsmentioning
confidence: 99%
“…In all of the previous figures, the reconstructions for the fullframe approach are achieved using an ADAM optimization procedure [Kingma and Ba 2014] with non-negativity constraints. This is analogous to Wirtinger flow optimization for phase retrieval [Candes et al 2014;Chakravarthula et al 2019]. We found that this approach works better than the classical optimization algorithm by Fienup [1982].…”
Section: Comparison To Alternative Algorithms and Limitationsmentioning
confidence: 86%
“…However, this method works well for amplitude holograms but needs improvements for phase-only and binary holograms [12,13]. Optimization of CGH using the Gerchberg-Saxton algorithm [14,15] and the gradient descent method [16] obtains a reconstructed image with good image quality, however, it is computationally expensive due to iterative calculations.…”
Section: Introductionmentioning
confidence: 99%